PENGEMBANGAN MEDIA PROMOSI KESEHATAN MERCHANDISE KIPAS MENGENAI GIZI SEIMBANG BAGI REMAJA (Jurnal Kesehatan Siliwangi, 2021)
Adolescents experience nutritional health problems caused by a healthy lifestyle. Efforts are made by providing nutrition health education using the media. The current media regarding nutrition ismedia leaflet. From a physical point of view, leaflets may not last long, spoil more quickly, are unattractive to read and easily lost when carried frequently. Development of Media Merchandise Fan Regarding Balanced Nutrition for adolescents is one of the means to assist and facilitate adolescents in learning about nutritional health which is the reason behind this development research. The purpose of this study was to develop and appropriate media merchandise fanregarding balanced nutrition for adolescents. The research used the ADDIE development model according to Robert Maribe Branch, namely Analysis, Design, Development, Implementation, and Evaluation. The results showed that the development ofhealth promotion media merchandise fanregarding balanced nutrition for adolescents from the media perspective, namely bright colors to attract attention, there are images that can help understand, fonts and sizes according to the character of teenagers. In terms of material, the content of the material is short, dense, clear and in simple language. The feasibility of health promotion media for merchandise fanregarding balanced nutrition for adolescents from the results of the study is that it is very suitable to be used with revisions as a balanced nutrition education medium for adolescents. This can be seen from the results of the percentage of material expert validation with a score of 86.7%, media expert validation with a score of 96.4% and adolescent respondents with a score of 90.8%.